1989
DOI: 10.1007/bf02370408
|View full text |Cite
|
Sign up to set email alerts
|

Effect of copper on stem melanosis and yield of wheat: Sources, rates and methods of application

Abstract: Park wheat (Triticum aestivum cv. Park) is susceptible to stem melanosis when grown on Cu-deficient soils. Three field experiments were conducted to evaluate the effectiveness of various Cu sources, using different methods and rates of application for reducing the incidence of stem melanosis and increasing the grain yield of Park wheat on a Cu-deficient Black Chernozemic soil in central Alberta. A fourth experiment determined the residual effect of Cu over 4 years. In the first experiment, Park wheat had less … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
16
0
1

Year Published

1995
1995
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 18 publications
1
16
0
1
Order By: Relevance
“…Previous field experiments on corn in Egypt have also indicated that use of corn seeds soaked in Zn, Mn and Fe solution could enhance NFUE leading to improvement in seed yield and N recovery (Teama 2001). However, it must be remembered that soil-applied Cu fertilizers at relatively high rates should have much longer-term residual effects on crop yield compared with foliar or seed-soaked Cu fertilizer treatments applied at low Cu rates (Gartrell 1980;Malhi et al 1989;Solberg et al 1996;Karamanos et al 1986Karamanos et al , 2005.…”
Section: Seed Yield and Cu Uptakementioning
confidence: 99%
See 4 more Smart Citations
“…Previous field experiments on corn in Egypt have also indicated that use of corn seeds soaked in Zn, Mn and Fe solution could enhance NFUE leading to improvement in seed yield and N recovery (Teama 2001). However, it must be remembered that soil-applied Cu fertilizers at relatively high rates should have much longer-term residual effects on crop yield compared with foliar or seed-soaked Cu fertilizer treatments applied at low Cu rates (Gartrell 1980;Malhi et al 1989;Solberg et al 1996;Karamanos et al 1986Karamanos et al , 2005.…”
Section: Seed Yield and Cu Uptakementioning
confidence: 99%
“…This suggests that dispersion and availability of Cu from the granules, especially from large granules , may be a major problem on farm fields. This also suggests that the lack of dispersion of Cu ions from granular Cu fertilizers and subsequently reduced Cu availability to crop plants can be overcome by application in the previous autumn (Karamanos et al 1986;Malhi et al 1989Malhi et al , 2005.…”
Section: Seed Yield and Cu Uptakementioning
confidence: 99%
See 3 more Smart Citations